Juridical analysis of breach of contract resolution in rural bank credit agreements - Fina Nurul Amanah; Mukhamad Nassir Agustiawan; Dian Samudra (Journal of Law Science, 2024)
This research aims to analyze the compliance of the Pandeglang District Court Decision No. 28/Pdt.G.S/2024/PN Pdl with Article 1239 of the Indonesian Civil Code (KUHPerdata) and to examine the judges’ legal considerations in resolving a breach of contract dispute in a credit agreement between a Rural Bank (BPR) and its debtor. This study employs a normative-empirical legal research method, combining statutory and case law analysis with field data obtained through court observation and interviews with judges and stakeholders. The study contributes theoretically by strengthening the understanding of contract law enforcement, particularly in verdicts rendered in absentia, and practically by providing guidance for judges and BPR institutions to ensure fair and consistent application of civil law. It also offers a methodological contribution by integrating normative and empirical approaches in assessing judicial decision making. This research is important because it ensures that judicial decisions in breach of contract cases reflect legal certainty, fairness, and consistency with civil law principles, especially in verdicts rendered in absentia.